Creutzfeldt-Jakob Disease after Dental Procedure along with the Initial Manifestations of Psychiatric Disorder: A Case Report - Badrfam, Rahim (Iran J Psychiatry, 2021)
Introduction: Creutzfeldt-Jakob disease (CJD) as a prion disease is an untreatable type of progressive neurodegenerative encephalopathy. Although no definitive case has been reported yet, here we report a case that given the history, course of symptoms, and recent dental practice, it is highly probable that it was caused by dental procedures. Case Report: The patient was a 52-year-old woman who has had memory problems gradually with forgetting the names of family members since 6 weeks prior to the visit and shortly after the dental procedure. She experienced progressive visual hallucinations accompanied by a sharp decline in cognitive, verbal, and motor abilities in just a few weeks. Finally, the diagnosis of Creutzfeldt-Jakob was made for her based on the clinical history and typical brain MRI. Discussion: Clinical evidence of this patient, along with positive brain MRI results, indicates the risk of prion transfer through dental procedures. Paying attention to the neurological aspects of psychiatric manifestations and increasing the awareness of dentists about how to deal with and act on the potential dangers of prion transfer is of paramount importance.